Ambiguous-Purpose Statements of Children and Other Victims of Abuse under the Confrontation Clause - Rothstein, Paul F (2015)
The author examines in this paper two kinds of ambiguous-purpose out-of-court statements that are especially problematic under current Confrontation law--problematic in ways that we hope will be solved directly or indirectly by the Supreme Court when it renders its decision in Ohio v. Clark. The statements he examines are: (1) Statements made by abused children concerning their abuse, for example to police, physicians, teachers, welfare workers, baby sitters, or family members, some of whom may be under a legal duty to report suspected abuse to legal authorities. At least some of these statements will be directly addressed by the Court in Ohio v. Clark. (2) Statements made by adult victims of sexual assaults to specially trained medical personnel (sometimes known as S.A.N.E. nurses or members of D.O.V.E. hospital units, or S.A.R.T. units) whose task is simultaneously to medically treat the victim and to gather or preserve evidence for a legal case or investigation. These statements may be inferentially address by the Court in Ohio v. Clark. U.S. Supreme Court Confrontation-Clause jurisprudence stemming from Crawford v. Washington (2004) holds that when a declarant (like the child or adult victim here) does not testify, her out-of-court statement’s admissibility against the alleged perpetrator in a criminal case is normally determined by what the “primary purpose” was when the statement was made, at least if it was made to law enforcement or its affiliates. If that “primary purpose” was prosecutorial or evidentiary the statement will ordinarily be inadmissible. If the purpose was something else—for example a primarily medical or treative purpose or a relatively immediate protective purpose or to deal with an on-going emergency—the statement is normally admissible insofar as the Confrontation Clause is concerned. The main problem with the victims’ and children’s statements identified above, is the difficulty in determining their “primary purpose.” Is it medical? Legal? Protective? Is it responding to an emergency? A related problem is whether the person to whom the statement was made had a substantial enough connection to law enforcement or government (if such connection is an independent requirement for there to be a Confrontation issue). A subsidiary question is whether there has to be anything like a questioning or interrogation—or some kind of formality attending the taking of the statement--in order for the Confrontation Clause to be applicable